The elephant from Baghdad - Holmes, Mary Tavener (Marshall Cavendish Children, 2012)
Relates the story, told by a monk named Notker the Stammerer, of how the Emperor Charlemagne sent an ambassador to Baghdad, the center of the Muslim world, to learn about the great ruler in the East, Haroun al Rashid. Includes notes on the factual basis of the story.